2019
DOI: 10.1021/acs.langmuir.9b00768
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ellipsometry and AFM To Probe Subnanometric Precursor Film Dynamics of Polystyrene Melts

Abstract: We investigate the evolution over time of the space profiles of precursor films spreading away from a droplet of polymer, in the poorly explored pseudo-partial wetting case. We use polystyrene melt droplets on oxidized silicon wafers. Interestingly, the film thicknesses measured by ellispometric microscopy are found in a 0.01 to 1 nm range. These thicknesses were validated by atomic force microscopy (AFM) measurements performed on the textured film obtained after a quench in temperature. From this, an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the present paper, we study the wetting of polybutadiene melts on oxidized silicon wafers, which experience conjoining interactions that tend to squeeze the precursor film (Π < 0): a motionless droplet coexists with the precursor film. This regime is called pseudopartial wetting and was evidenced for high polarizability polymers. , We will show that depositing polybutadiene droplets on such surfaces is a way to prepare precursor films of low density, which smoothly decay over an extended lateral region. We will characterize the precursor film profiles and dynamics by ellipsometry and show that the chains in the film obey a diffusion equation.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In the present paper, we study the wetting of polybutadiene melts on oxidized silicon wafers, which experience conjoining interactions that tend to squeeze the precursor film (Π < 0): a motionless droplet coexists with the precursor film. This regime is called pseudopartial wetting and was evidenced for high polarizability polymers. , We will show that depositing polybutadiene droplets on such surfaces is a way to prepare precursor films of low density, which smoothly decay over an extended lateral region. We will characterize the precursor film profiles and dynamics by ellipsometry and show that the chains in the film obey a diffusion equation.…”
mentioning
confidence: 86%
“…Atomic force microscopy showed that the precursor films have no texture. 43 The typical spreading of a precursor film of PBd 1,4 around a sessile droplet of radius r d ≃ 100 μm at short times is shown in Figure 1. A few minutes after the deposition of the droplet, the contact line stops, while a film spontaneously spreads around the droplet.…”
mentioning
confidence: 98%
See 3 more Smart Citations